Iron deficiency and supplementation in heart failure - Lakhal-Littleton, S; Cleland, JGF (Springer Nature, 2024)
Non-anaemic iron deficiency (NAID) is a strategic target in cardiovascular medicine because of its association with a range of adverse effects in various conditions. Endeavours to tackle NAID in heart failure have yielded mixed results, exposing knowledge gaps in how best to define ‘iron deficiency’ and the handling of iron therapies by the body. To address these gaps, we harness the latest understanding of the mechanisms of iron homeostasis outside the erythron and integrate clinical and preclinical lines of evidence. The emerging picture is that current definitions of iron deficiency do not assimilate the multiple influences at play in patients with heart failure and, consequently, fail to identify those with a truly unmet need for iron. Additionally, current iron supplementation therapies benefit only certain patients with heart failure, reflecting differences in the nature of the unmet need for iron and the modifying effects of anaemia and inflammation on the handling of iron therapies by the body. Building on these insights, we identify untapped opportunities in the management of NAID, including the refinement of current approaches and the development of novel strategies. Lessons learned from NAID in cardiovascular disease could ultimately translate into benefits for patients with other chronic conditions such as chronic kidney disease, chronic obstructive pulmonary disease and cancer.